Projection of Health Sector Workforce Requirement: Vision 2025 - Gholamhossein Salehi Zalani; Azad Shokri; Elmira Mirbahaeddin; Tahereh Kashkalani; Roghayeh Khalilnezhad; Mahboubeh Bayat (Tehran University of Medical Sciences, 2021)
Background: This study was conducted with a long-term vision (2014-2025) targeted workforce requirement projection by occupational groups in Iran's health sector. Methods: The "modified & combined model" used including Hall Model and Australian health workforce estimation model. It was a need-based approach with three components of estimation; requirements, supply with current growth and net required workforce. Requirement estimated by three assumptions: active workforce calculation; the growth of health service delivery resources and facilities; and daily individual working hours, created eight different scenarios. Economic feasibility of each scenario determined. To forecast the supply, used accurate numbers of the existing pool of practicing workforce in addition to inflows, minus losses from the profession. To calculate total recruits required, base year stock deducted from projected requirement and by adding Net flow, recruits required calculated. Results: The health sector will need 781,887 workforces to realize service's needs. Workforce supply with the existing trend in the target year was 799,347. Therefore, workforce balance would be 17,460 surpluses. Moreover, to estimate required workforce and substitution number for the exited ones during the study periods till the target year, 547,136 individuals should be recruited mostly nurses and physicians. Conclusion: Limiting the workforce required to economic feasibility challenge workforce accessibility in the future as it is sensed in present tense as well. Therefore, in addition augmenting GDP and health funds, it is necessary alternative policies such as increasing share of health sector from GDP, prioritization of workforce needs or moving towards other proper policies.